Faceless heroes: A content analysis of determinants for the recruitment, career development & retention of Emergency Medical Dispatchers in the United States of America - McAleavy, Tony; Choi, Byunggi; Arlikatti, Sudha (International journal of disaster risk reduction, 2021)
Emergency Medical Dispatchers (EMDs) provide life-critical telephone-based medical advice 24 h a day, 365 days a year. EMDs are the first point of contact but rarely, if ever, meet the public whom they serve. They are detached from the scene and less visible than their first responder colleagues, but subject to comparable levels of stress and secondary trauma: they are our faceless heroes. In recent years, recruitment and retention levels are falling: candidates are dropping out before completing their training due to early burnout. Despite their key role, scant attention has been paid to this area of research. This study aims to fill this gap by identifying contributory factors that affect recruitment, career development and retention of EMDs and suggesting improvements to practice. Interpretivism underpinned 11 inductive interviews focused on EMD recruitment, career development and retention. The resultant qualitative data were transcribed verbatim, and then subjected to content analysis using the computer-assisted qualitative data analysis software Atlas. ti. Content analysis resulted in 20 thematic codes, which were refined into seven categories – recruitment, training and career development, required systemic enhancements, role stress, ideal EMD, esprit de corps and optimum skillset - articulated as the optimum skill-set theory. These informed one comprehensive network diagram and two tables to illustrate the links between the codes and categories, explicated by participant quotations. They also elaborate on the theoretical and practical contributions made by the study which provide critical insights for recruiters, in-career EMD and those interested in pursuing a career as an EMD.